2016
DOI: 10.2514/1.b35835
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Facility Effects on Hall-Effect-Thruster Cathode Coupling: Discharge Oscillations and Facility Coupling

Abstract: The physical mechanisms that govern the electrical interaction between the Hall-effect-thruster electrical circuit and the conductive vacuum-facility walls are not fully understood. As a representative test bed, an Aerojet Rocketdyne T-140 Hall-effect thruster is operated at 3.05 kW and a xenon mass flow rate of 11.6 mg∕s with a vacuum facility operating neutral pressure of 7.3 × 10 −6 torr, corrected for xenon. Two electrical witness plates, representative of the facility chamber walls, are placed 2.3 m radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Matching volumetric flow rates results in the injection of the same number of neutral particles during both xenon and krypton operations, thereby yielding equivalent near-field pressures for similar neutral temperatures [45]. This pressure equivalency is important because previous work indicated that electrical facility effects may be sensitive to the neutral pressure distribution in the facility [28,48]. The choice to match either mass flow rates or discharge powers (which are the two other common methods for krypton operation) was avoided because it would have yielded an increase in number density of 25-60%, and therefore could have resulted in the conflation of electrical and backpressure effects and altered the relative current collected by the axial and radial plates [28,45,48].…”
Section: Results and Discussion: Het-plate Couplingmentioning
confidence: 99%
See 4 more Smart Citations
“…Matching volumetric flow rates results in the injection of the same number of neutral particles during both xenon and krypton operations, thereby yielding equivalent near-field pressures for similar neutral temperatures [45]. This pressure equivalency is important because previous work indicated that electrical facility effects may be sensitive to the neutral pressure distribution in the facility [28,48]. The choice to match either mass flow rates or discharge powers (which are the two other common methods for krypton operation) was avoided because it would have yielded an increase in number density of 25-60%, and therefore could have resulted in the conflation of electrical and backpressure effects and altered the relative current collected by the axial and radial plates [28,45,48].…”
Section: Results and Discussion: Het-plate Couplingmentioning
confidence: 99%
“…Although the current collection by the facility walls is controlled by the wall sheath and does not impact quasi-neutrality in the plume, this alternate electron recombination pathway is an artificial effect introduced by the presence of the vacuum facility that is expected to be absent on orbit. Furthermore, previous work has confirmed that the presence of this alternate pathway can alter processes dependent on the electron path through the plasma, such as cathode coupling and plasma reactance, [26][27][28][29].…”
mentioning
confidence: 84%
See 3 more Smart Citations